Acute Myeloid Leukemia in Children: Emerging Paradigms in Genetics and New Approaches to Therapy - Conneely, Shannon E. (Curr Oncol Rep, 2021)
PURPOSE OF REVIEW: Acute myeloid leukemia (AML) in children remains a challenging disease to cure with suboptimal outcomes particularly when compared to the more common lymphoid leukemias. Recent advances in the genetic characterization of AML have enhanced understanding of individualized patient risk, which has also led to the development of new therapeutic strategies. Here, we review key cytogenetic and molecular features of pediatric AML and how new therapies are being used to improve outcomes. RECENT FINDINGS: Recent studies have revealed an increasing number of mutations, including WT1, CBFA2T3-GLIS2, and KAT6A fusions, DEK-NUP214 and NUP98 fusions, and specific KMT2A rearrangements, which are associated with poor outcomes. However, outcomes are starting to improve with the addition of therapies such as gemtuzumab ozogamicin and FLT3 inhibitors, initially developed in adult AML. SUMMARY: The combination of advanced risk stratification and ongoing improvements and innovations in treatment strategy will undoubtedly lead to better outcomes for children with AML.